Effectiveness of ivermectin mass drug administration in the control of soil-transmitted helminth infections in endemic populations: a systematic review and meta-analysis - Brandon Le; Naomi E. Clarke; Nicolas Legrand; Susana Vaz Nery (BMC, 2024)
Abstract Background Current soil-transmitted helminth (STH) control guidelines endorse the use of albendazole or mebendazole for school-based targeted preventive chemotherapy (PC), yet their reduced efficacy against Strongyloides stercoralis and Trichuris trichiura presents significant limitations. Emerging evidence indicates that community-wide PC [or mass drug administration (MDA)] using ivermectin, commonly used in other neglected tropical disease (NTD) control programs, may play an important role in controlling these parasites. We conducted a systematic review and meta-analysis to evaluate the effectiveness of ivermectin PC in reducing STH prevalence in endemic populations. Methods We searched Pubmed, EMBASE, and Web of Science on February 14, 2023, for studies that investigated the effectiveness of ivermectin PC, either alone or in combination with other anthelmintic drugs, on STH infections, and provided a measure of STH prevalence before and after PC. We calculated pooled prevalence reductions for each STH using random-effects meta-analyses. Our protocol is available on PROSPERO (registration number CRD42023401219). Results A total of 21 were eligible for the systematic review, of which 15 were eligible for meta-analysis. All studies delivered ivermectin through MDA. The pooled prevalence reduction of S. stercoralis following MDA with ivermectin alone was 84.49% (95% CI 54.96-94.66) across five studies and 81.37% (95% CI 61.62-90.96) across seven studies with or without albendazole. The prevalence reduction of T. trichiura was 49.93% (95% CI 18.23-69.34) across five studies with ivermectin alone, and 89.40% (95% CI 73.66-95.73) across three studies with the addition of albendazole. There was high heterogeneity for all syntheses (I 2 > 65%). Conclusions This study underscores the key role of ivermectin-based MDA in addressing limitations in current global STH guidelines in terms of limited efficacy against S. stercoralis and T. trichiura. Based on these findings, revising international STH guidelines to include ivermectin is a promising option to progress the control and eventual elimination of STHs and other NTDs.